Lymphoma, a great imitator in neurology. (March 2020) - Yeh, Wei Zhen; Muthusamy, Subramanian; McKelvie, Penny; Collins, Steven; French, Ann; Filshie, Robin; Sutherland, Tom; Trost, Nicholas; Reardon, Katrina
Highlights: We report three cases of lymphoma mimicking sarcoidosis, vasculitis and infection. Lymphoma can have protean manifestations. Obtaining tissue is key to diagnosis. Elevated serum ACE is poorly sensitive and insufficiently specific for sarcoidosis. In the diagnosis of intravascular lymphoma, random skin biopsy can be considered. Structural and metabolic imaging have complementary roles in lymphoma evaluation. Abstract: The title "great imitator" refers to conditions which can cause varied manifestations and mimic many diseases. Lymphoma is worthy of this title. We describe three cases of lymphoma in which lymphoma mimicked other diseases causing neurological dysfunction, specifically sarcoidosis, vasculitis and infection respectively. Case 1 was a 66-year-old man with subacute progressive diplopia and gait disturbance and investigations revealing a supratentorial para -falcine soft tissue lesion, mid-thoracic cord enhancement and right axillary mass and an elevated serum ACE. Right axillary mass core biopsy was diagnostic of Burkitt lymphoma. Case 2 was a 50-year-old man with several weeks of constitutional symptoms and development of lower limb weakness and numbness, urinary retention and confusion while in hospital. MRI brain demonstrated multi-territory cerebral infarcts. Intravascular lymphoma was diagnosed on random skin biopsy. Case 3 was a 65-year-old man with several weeks of headache and diplopia on a background of previously treated Burkitt lymphoma. CSF analysis showed a lymphocytic pleocytosis and markedly low glucose with cytologic analysis negative for malignancy. Investigations for an infective cause were negative. FDG-PET demonstrated marked, disseminated spinal and cranial leptomeningeal disease and a multi-focal, intra-dural relapse of Burkitt lymphoma was diagnosed. The varied manifestations in our cases demonstrate the ability for lymphoma to mimic infective, inflammatory, granulomatous (including sarcoidosis) and neoplastic aetiologies. An elevated serum ACE appears insufficiently diagnostic to confirm sarcoidosis and tissue for histological examination should be sought whenever possible. When the diagnosis is uncertain, the possibility of this great imitator should be considered, especially for multi-focal disease.